OPTIMALISASI PEMANFAATAN DAN DIVERSIFIKASI OLAHAN PANGAN LOKAL SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT - Kurniyati, Yuli; Rahmawati, Fitri; Suryati, Pulut (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The purpose of this activity is the program: (1) increasing knowledge about the members of KWT good food and a variety of local food processing; (2) improve the skills of the local food processing production process; (3) improve the skills and knowledge of the packaging and labeling of interest; (4) increasing knowledge about the ins and outs of administrative partner KWT; (5) improve knowledge of financial management and sales price calculation method; (6) motivate and increase knowledge of productive business activities (entrepreneurship); and (7) increase knowledge of marketing through the internet . The method used in this service activity is socialization, training, and mentoring.The results of this activity is the increased knowledge, understanding and skills of participants in the field of diversified local food processing and the production of local food processing, packaging and labeling of interest, KWT administration, business financial management, entrepreneurship, and marketing through the internet, it is seen from indicators: (1) members KWT producing snacks (snack) to be deposited into the stalls; (2) set up shop Romadhon; (3) completion of the financial administration of the organization and administration of KWT; (4) the creation of KWT stalls as a member of the marketing group produki; (5) blog KWT as media marketing on line and card-making nama; (6) snack orders increase for members of KWT Keywords : diversification, local food, and processing